Kritik terhadap Perspektif Dominan (Perspekif Komunikasi Pembangunan) - Wulan Oktariani (Universitas Islam Negeri Imam Bonjol Padang, 2014)
It can not be deny that technological advances affect how much a company may be better known by the public. Just in seconds information can be quickly accepted by the public only by using communication technologies such as mobile phones at their disposal. Because it is a public relations practitioner who became a central position in a company in terms of dissemination of information on demand creative and innovative master the technological progress. The ability to respond quickly to all the information that is accompanied with using mastery of technology tools are essential. This study focuses on the role of Public Relations in Bank BNI Syariah in the use of Internet media, especially in the use of the company's website as a tool to facilitate the relationship between the company and the community, especially customers in order to disseminate information about the aspects which are owned by their company, ranging from company profiles, history of the company, product information, even to the career information in Bank BNI Syariah.